Senam Kreatif Anak Usia Dini Sebagai Upaya Meningkatkan Daya Tahan Tubuh dan Kesehatan di Sekolah Citra Kasih Ambon - Marsiline Pieter; Corneli Gaite (Lembaga Pengembangan Kinerja Dosen, 2025)
Early childhood represents a critical stage of rapid growth and development, during which children require appropriate stimulation to optimize both their physical health and overall well-being. One effective approach to meet these developmental needs is through engaging and enjoyable physical activities. Creative gymnastics, which combines rhythmic movements with music, offers a practical and appealing method to strengthen children’s immune systems while simultaneously fostering the development of gross motor skills. This community service program was implemented at Early Childhood Education (ECE) Citra Kasih School, Ambon, and involved children aged 4–6 years. The method of implementation emphasized direct practice, where children actively participated in a series of simple, structured, and playful movements accompanied by cheerful music, making the activity easy to follow and enjoyable. Observations during the program indicated that children showed a higher level of enthusiasm, increased activeness, and notable improvements in stamina, balance, and movement coordination. In addition, teachers expressed positive responses, highlighting the added value of integrating structured physical activities into the learning environment. The program not only benefited the children physically but also provided educators with new insights on effective strategies to support children’s health. Therefore, creative gymnastics can be recommended as a routine school activity to strengthen immunity, improve physical endurance, and promote healthy lifestyles in early childhood.